Branch retinal artery occlusion from laser pointer misuse - Aseel Gebara; Brice Nguedia Vofo; Tareq Jaouni (American Journal of Ophthalmology Case Reports)
Purpose: To report a case of branch retinal artery occlusion (BRAO) following exposure to a blue laser pointer in a healthy 22-year-old male. Observations: A 22-year-old healthy male presented with sudden visual field impairment in his right eye, occurring 18 hours after exposure to a blue laser pointer. He complained of an immediate persistent curtain-like obstruction in the upper visual field of the affected eye. Clinical examinations revealed BRAO in the inferior half of the retina, confirmed by Optical coherence tomography (OCT) showing edema. Fluorescein angiography indicated delayed filling and a focal hyperfluorescence area, consistent with a leak. Due to a lack of established management, the patient was offered follow-up care. Though reperfusion was observed on fluorescein angiography one month later, thinning of the retinal layers was evident on OCT, and there was no visual recovery. Conclusions and Importance: In conclusion, laser pointers, though often considered innocuous, can lead to serious ocular damage. The clinical implications of laser-induced retinal injury are severe and sometimes irreversible, warranting special attention. The observed clinical course underscores the complex nature of such injuries and emphasizes the importance of awareness and caution regarding laser pointer use.